2011
DOI: 10.3727/096368910x519292
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Periodontal Stem Cell Transplantation in the Treatment of Advanced Periodontitis

Abstract: Periodontitis is the most common cause for tooth loss in adults and advanced types affect 10-15% of adults worldwide. The attempts to save tooth and regenerate the periodontal apparatus including cementum, periodontal ligament, and alveolar bone reach to the dental tissue-derived stem cell therapy. Although there have been several periodontitis models suggested, the apical involvement of tooth root is especially challenging to be regenerated and dental stem cell therapy for the state has never been investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
179
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(184 citation statements)
references
References 58 publications
2
179
0
Order By: Relevance
“…More recently, both allogeneic and autologous transplanation of PDLSCs in a swine model for periodontitis resulted in the regeneration of the periodontal tissue [82,95]. Similar experiments in a dog model of periodontitis have compared the regenerative capacity of three different types of dental MSCs in autologous transplantation and demonstrated that PDLSCs have the best regeneration capacity over DPSCs and DFPCs [96]. DFPCs comprise another type of dental MSCs that were identified in the dental follicle [83].…”
Section: Therapeutic Applications Of Ncscs: Mscsmentioning
confidence: 94%
“…More recently, both allogeneic and autologous transplanation of PDLSCs in a swine model for periodontitis resulted in the regeneration of the periodontal tissue [82,95]. Similar experiments in a dog model of periodontitis have compared the regenerative capacity of three different types of dental MSCs in autologous transplantation and demonstrated that PDLSCs have the best regeneration capacity over DPSCs and DFPCs [96]. DFPCs comprise another type of dental MSCs that were identified in the dental follicle [83].…”
Section: Therapeutic Applications Of Ncscs: Mscsmentioning
confidence: 94%
“…(13) In an in vivo study, dental tissue-derived adult stem cells, including DPSC and PDLSC were autologous transplanted into the apical involvement defect. (14) PDLSCs showed the best regenerating capacity of periodontal ligament, alveolar bone, and cementum as well as peripheral nerve and blood vessel, which were evaluated by conventional immunohistology, 3D micro-CT and clinical index. (14) PDLSC is suggested as a favorable candidate for the clinical application, that can be used for treatment of advanced periodontitis where tooth removal was indicated in the clinical cases.…”
Section: Cd117mentioning
confidence: 99%
“…Furthermore, human PDLSCs that were transplanted into surgically created defects at the periodontal area of mandibular molars in immunocompromised rats were integrated into the PDL tissue, resulting in homing on the surfaces of alveolar bone and tooth root (Seo, et al, 2004). Swine or canine PDLSCs have also been reported to regenerate PDL tissues when transplanted into surgically created periodontal defect areas in swine or canine models (Liu et al, 2008;Park et al, 2010). Immunomodulatory property is also known to be one of the characteristics of MSCs (Bartholomew et al, 2002).…”
Section: Characteristics Of Pdl Stem Cellsmentioning
confidence: 99%